The effects of the healthcare line in a stroke unit: three years' experience of a center in the Northeast of Brazil - Deborah Moreira Rangel; Anna Karuza Nogueira Feitosa; Flaviane Melo Araújo; Mara Cibelly da Silva Pinheiro; Alan Alves de Lima Cidrão (Arquivos de Neuro-Psiquiatria)
Background Treatment at an organized stroke unit center (SUC) improves survival after stroke. Stroke mortality has decreased worldwide in recent decades.